The Institutionalization of Public Innovation: Evidence from Indonesia - Pradana, I Putu Yoga Bumi; Kumorotomo, Wahyudi; Susanto, Ely (SAGE Publications Inc., 2023)
This study examines critical factors contributing to institutionalizing creative ideas into a formal innovation and their difference in the regulatory-pillar output of innovation, which public sector innovation academics (PSI) rarely explore. Using multiple case study methods, this study interviewed 23 informants involved in four innovation cases in two local governments in Indonesia. This study highlighted nine critical factors in institutionalizing public innovation categorized into four dimensions: leadership, intraorganizational, innovation candidate attributes, and external environment. This study’s novel contribution lies in identifying critical factors shaping and the outputs of institutionalization of public innovation. © The Author(s) 2023.